Double-MXene concerted catalytic magnesium hydride hydrogen storage material and preparation method thereof

Through dual MXENE collaborative catalytic strategies, the problem of MGH2 high -hydrogenation temperature and slow hydrogen dynamics have been solved, it has significantly improved its hydrogen storage performance, and achieves the effect of rapidly release and absorb hydrogen at low temperature.

CN119349506APending Publication Date: 2025-01-24CHENGDU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411550126.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The high dehydrogenation temperature of MgH2, slow hydrogen adsorption/desorption kinetics, and poor cycling stability limit its application in hydrogen storage.

Method used

The dual MXENE collaborative catalytic strategy is used to compose NB2ALC and TI3ALC2 to prepare NB2C and Ti3C2 MXENE materials through one -step method, and remove the official group through thermal treatment, and then compound the ball mill with MGH2 to form dual MXENE collaborative catalytic hydrogen hydrogen storage materials.

Benefits of technology

It significantly improves the hydrogen absorption rate and hydrogen release rate of MgH2, improves the hydrogen storage performance, and can quickly release and absorb large amounts of hydrogen at low temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349506A_ABST
    Figure CN119349506A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a double-MXene synergistic catalytic magnesium hydride hydrogen storage material. The preparation method comprises the following steps: S1, etching Nb2AlC and Ti3AlC2 by using a hydrofluoric acid aqueous solution through a one-step method to prepare two MXene materials of Nb2C and Ti3C2; s2,-F functional groups in Nb2C and Ti3C2 are removed through heat treatment,-OH is converted into-O, and MXene materials including Nb2C / C and Ti3C2 / C are obtained; s3, Nb2C / C, Ti3C2 / C and MgH2 are compounded through a ball milling method, and the double-MXene concerted catalysis magnesium hydride hydrogen storage material is prepared. The invention also discloses the double-MXene synergistic catalytic magnesium hydride hydrogen storage material prepared by the preparation method. The preparation method disclosed by the invention is simple and efficient, the cost is reduced, and the hydrogen absorption rate and hydrogen desorption rate of MgH2 are remarkably improved through synergistic catalysis of double MXene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen storage materials, and in particular to a double MXene synergistic catalytic magnesium hydride hydrogen storage material and a preparation method thereof. Background Art

[0002] With the increasing depletion of global oil resources and the intensification of the energy crisis, the sustainable development of social economy urgently needs new green energy solutions with less impact on the environment. Among many new energy sources, hydrogen energy is regarded as an effective way to reduce greenhouse gas emissions and air pollution because of its zero-emission characteristics. The effective storage of hydrogen energy is the key to the practical application of hydrogen energy, but it is also the main bottleneck of hydrogen energy application. At present, although the high-pressure gaseous hydrogen storage technology is mature, its potential leakage and explosion risks cannot be ignored; while liquid hydrogen storage technology faces the problem of high energy consumption and energy loss during low-temperature liquefaction. In contrast, solid-state hydrogen storage technology forms metal hydrides or coordinated hydrides through the interaction between hydrogen and materials, showing higher hydrogen storage capacity and superior safety, so it is widely regarded as the most promising hydrogen storage technology direction. Magnesium and its hydride (Mg / MgH2) are an ideal solid-state hydrogen storage material. They are not only environmentally friendly and resource-rich, but also have a high weight hydrogen storage capacity. Under ideal conditions, the theoretical hydrogen storage capacity of pure magnesium (Mg) can reach 7.6wt%. Therefore, it is regarded as a potential hydrogen storage material and an ideal hydrogen source for portable fuel cells. It shows great potential in promoting the application of hydrogen energy technology in portable power systems.

[0003] However, the practical application of MgH2 is limited by its high dehydrogenation temperature, slow hydrogen adsorption / desorption kinetics, and poor cyclic stability. First, as an ionic compound, the adsorption and desorption process of MgH2 involves the formation and breaking of H and Mg-H chemical bonds, as well as changes in the crystal structure, which means that the temperature of MgH2 needs to reach 300°C before it can quickly release hydrogen. Second, when hydrogen molecules adsorb onto the surface of MgH2, they need to overcome a relatively high adsorption energy barrier, that is, the activation energy. This means that the process of hydrogen adsorption requires sufficient energy, which makes the adsorption reaction relatively slow. Third, in multiple hydrogenation and dehydrogenation cycles, reaction by-products such as MgO may gradually accumulate on the surface, causing the material to agglomerate, reduce the contact area, limit the reaction, and reduce the reaction rate, inhibiting hydrogen diffusion and weakening the hydrogen storage performance, thereby causing the material's cyclic stability to decrease.

[0004] Therefore, it is urgent to solve these problems of MgH2. To solve these problems, researchers can significantly reduce the initial dehydrogenation temperature and increase the rate of hydrogen absorption / desorption by introducing an appropriate amount of catalyst into the reaction system. In this process, the catalyst plays a vital role, which can effectively improve the rate of hydrogen production from MgH2.

[0005] Among the many catalyst options, a new type of two-dimensional framework catalyst has gradually entered the public's field of vision - MXene. MXene is a new type of two-dimensional transition metal carbide or nitride with a molecular formula of M n+1 X n T x , where M is a transition metal, including Ti, Sc, Cr, V, Zr, Nb and Mo, X is carbon or nitrogen, T x Represents the surface end, including -F, -OH and -O groups. Its structure is usually composed of multiple thin layers of atomic sheets, similar to the graphene structure. This material can provide more channels for the movement of ions and greatly increase the movement speed of ions.

[0006] Scientific research has confirmed that in 2016, Liu, YF introduced Ti3C2 MXene into MgH2 for the first time. The two-dimensional Ti3C2 (MXene) synthesized by exfoliating Ti3AlC2 powder showed excellent effects in improving the catalytic activity of MgH2 hydrogen storage reaction, significantly reducing the required temperature for hydrogen release and absorption. Lu, CL significantly reduced the initial hydrogen desorption temperature of magnesium hydride (MgH2) from 318℃ to 190℃ by adding two-dimensional vanadium carbide (V2C) MXene as a catalyst, and made the MgH2+10wt% V2C composite release 6.4wt% hydrogen within 10 minutes at 300℃, while maintaining good cycle stability. The results show that V2C helps to shorten the bond length of Mg-H, facilitates the destabilization of MgH2, and has a dual effect on the kinetics and thermodynamics of MgH2 hydrogen desorption. The results show that the addition of MXene can adjust the reaction kinetics. Wang, ZY et al. synthesized a new two-dimensional layered NbTiC MXene from the MAX phase by a wet chemical etching process and introduced it into MgH2 by ball milling, forming NbTi bimetallic nanocrystals in situ. The initial dehydrogenation temperature of the MgH2-9 wt% NbTiC sample was reduced to 195°C, and 5.8wt.% of H2 could be released within 30 minutes at 250°C. After complete dehydrogenation, 4.0wt.% of H2 can be rehydrogenated and absorbed within 15 minutes at 50°C. The results show that in the NbTi cluster, the charge is transferred from Ti atoms to Nb atoms, and the absolute value of the adsorption energy of H2 on NbTi is low, which is conducive to the breaking of the Mg-H bond and the separation of H2 from the NbTi surface, resulting in good catalytic activity. Liu prepared the two-dimensional Nb4C3T x (MXene) applied to MgH2. Activated MgH2-5wt% Nb4C3T xThe composite material can release 90% (~5.45wt%) of the maximum hydrogen capacity within 385s at 250°C. In addition, when the dehydrogenation temperature reaches 300°C, the dehydrogenation time of pure Mg must be greater than 2h. x The apparent activation energy of dehydrogenation of the composite material is 81.2 kJ / mol H2, which is much lower than that of spherical pure magnesium (153.8 kJ / mol H2). After dehydrogenation, the sample can absorb about 3.50 wt% of hydrogen in 2 hours at a temperature as low as 50 degrees Celsius, and the apparent activation energy of hydrogenation is reduced to 27.8 kJ / mol H2, which is much lower than that of pure magnesium after dehydrogenation (82.1 kJ / mol H2). x Such excellent hydrogen storage kinetics and low energy barrier in the MgH2 hydrogen storage reaction indicate that it has high catalytic activity, which may be related to the unique layered structure and in-situ formed NbH x This study expands the knowledge on designing efficient catalysts via two-dimensional MXenes in hydrogen storage materials.

[0007] In summary, including Ti3C2, V2C, Nb4C3T x MXenes such as NbTiC as catalysts show excellent catalytic activity for MgH2 hydrogen storage performance, which not only significantly reduces the temperature required for hydrogen absorption and release, but also can adjust the kinetics. At present, researchers are focusing more on Ti-based MXenes materials, Ti3C2T x The preparation technology of MXene is quite mature. However, in MXene materials, as the number of atomic layers increases, the molecular weight increases and the theoretical capacity decreases. Therefore, compared with Ti3C2T x In comparison, MXene with M2X structure has higher specific capacity. Among many MXenes materials, Nb2CT x It exhibits excellent conductivity, close to zero band gap, and has special metallic properties due to the flexible combination of surface functional groups. It should be noted that due to the special structure and strong metallic properties of the Nb element, the bond between niobium and aluminum in Nb2AlC may be stronger than the bond between titanium and aluminum in Ti3AlC2, so a longer etching time is required to obtain Nb2C. Summary of the invention

[0008] In view of the above problems, the present invention aims to provide a method for preparing a double MXene synergistic catalytic magnesium hydride hydrogen storage material, which is simple and efficient, reduces the cost, and significantly improves the hydrogen absorption rate and hydrogen release rate of MgH2 through double MXene synergistic catalysis.

[0009] The technical solution of the present invention is as follows:

[0010] In one aspect, the present invention provides a method for preparing a double MXene synergistic catalytic magnesium hydride hydrogen storage material, comprising the following steps:

[0011] S1, using hydrofluoric acid aqueous solution to etch Nb2AlC and Ti3AlC2 in a one-step method to prepare two MXene materials, Nb2C and Ti3C2;

[0012] S2, by heat treatment, the -F functional groups in Nb2C and Ti3C2 are removed respectively, and -OH is converted into -O to obtain MXene materials: Nb2C / C and Ti3C2 / C;

[0013] S3, Nb2C / C, Ti3C2 / C and MgH2 were compounded by ball milling to prepare double MXene synergistic catalytic magnesium hydride hydrogen storage material.

[0014] Preferably, in step S1, one-step etching of Nb2AlC using a hydrofluoric acid aqueous solution comprises the following steps: mixing an excess of 40% hydrofluoric acid aqueous solution with Nb2AlC powder, stirring at 60°C for 70 hours, centrifuging and washing until the pH value of the supernatant is 6-7, and then filtering, and freeze-drying the obtained precipitate A for 24-70 hours to obtain Nb2C powder.

[0015] Preferably, in step S1, one-step etching of Ti3AlC2 using hydrofluoric acid aqueous solution includes the following steps: mixing an excess of 40% hydrofluoric acid aqueous solution with Ti3AlC2 powder, stirring at 60°C for 24 hours, centrifuging and washing until the pH value of the supernatant is 6-7, and then filtering, and freeze-drying the obtained precipitate B for 24-70 hours to obtain Ti3C2 powder.

[0016] Preferably, centrifuge is used for centrifugation at a speed of 10000 rpm, and then deionized water is used for multiple washings until the pH value of the supernatant is 6-7.

[0017] Preferably, in step S2, the heat treatment step is: respectively put Nb2C powder and Ti3C2 powder into a crucible, then put the crucible into a tube furnace filled with inert gas, and heat at 600°C and a heating rate of 4°C·min -1 and annealed for 6 h under the conditions of , and Nb2C / C powder and Ti3C2 / C powder were obtained respectively.

[0018] Preferably, in step S3, the ball milling step is: mixing Nb2C / C powder and Ti3C2 / C powder in a mass ratio of 1:1-2 to obtain a dual catalyst mixed powder, adding the dual catalyst mixed powder to magnesium hydride powder to obtain mixture A, and then pouring mixture A into a ball mill for ball milling.

[0019] Preferably, the dual catalyst mixed powder is added to the magnesium hydride powder at a weight percentage of 3wt%-7wt%.

[0020] Preferably, the ball mill is a planetary ball mill; the mixture A is poured into the planetary ball mill and mechanically ball-milled at a rotation speed of 400 rpm for 10-20 hours; the ball-to-material mass ratio of the ball mill is 40:1.

[0021] Preferably, the cycle program of the ball mill is set to rotate forward for 15 minutes, stop for 15 minutes, reverse for 15 minutes, and stop for 15 minutes, and the cycle is alternately operated.

[0022] On the other hand, a high-efficiency double MXene synergistic catalytic magnesium hydride hydrogen storage material is provided, which is obtained by the preparation method of the double MXene synergistic catalytic magnesium hydride hydrogen storage material described above.

[0023] The beneficial effects of the present invention are:

[0024] 1. The present invention adopts a one-step etching process to prepare MXene at low temperature (less than 80°C), which simplifies the preparation process of MXene, reduces costs and improves preparation efficiency.

[0025] 2. The present invention can effectively remove the -F functional group in Nb2C and Ti3C2 through heat treatment, and convert -OH into -O, which is beneficial to expose more active centers, increase active sites, and improve the activity of the catalyst.

[0026] 3. The dual MXene synergistic catalytic strategy of the present invention significantly improves the hydrogen absorption / desorption kinetics of MgH2 and enhances the hydrogen storage performance.

[0027] 4. The dual MXene-catalyzed MgH2 of the present invention can quickly release and absorb a large amount of hydrogen at low temperatures, showing excellent hydrogen storage kinetics. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 X-ray diffraction spectra of Nb2C / C and Nb2AlC prepared in Example 1 of the present invention;

[0029] Figure 2 X-ray diffraction spectra of Ti3C2 / C and Ti3AlC2 prepared in Example 1 of the present invention;

[0030] Figure 3 This is a scanning electron microscope image of Ti3C2 / C prepared in Example 1 of the present invention;

[0031] Figure 4 is a scanning electron microscope image of Nb2C / C prepared in Example 1 of the present invention;

[0032] Figure 5 This is an energy dispersive X-ray spectrum image of Ti3C2 / C prepared in Example 1 of the present invention;

[0033] Figure 6 This is an energy dispersive X-ray spectrum image of Nb2C / C prepared in Example 1 of the present invention;

[0034] Figure 7 The hydrogen release curves of the samples prepared in Examples 1-3 and Comparative Examples 1-2 of the present invention;

[0035] Figure 8 : are hydrogen release curves of samples prepared in Examples 1, 4 and 5 of the present invention;

[0036] Fig. 9 The hydrogen absorption curves of the samples prepared in Examples 1-3 and Comparative Examples 1-2 of the present invention;

[0037] Fig.10 The hydrogen absorption curves of the samples prepared in Examples 1, 4 and 5 of the present invention;

[0038] Fig.11 This is a flow chart for the preparation of dual MXene synergistic catalytic magnesium hydride hydrogen storage materials in a specific embodiment. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with the accompanying drawings and examples, but it is not intended to limit the scope of the present invention, and is only illustrative. It should be noted that, in the absence of conflict, the embodiments in the present application and the technical features in the embodiments can be combined with each other. Unless otherwise specified, all technical and scientific terms used in this application have the same meanings as those of ordinary skill in the art to which this application belongs. The experimental methods used in the following examples are conventional methods unless otherwise specified. Materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.

[0040] The present invention provides a method for preparing a double MXene synergistic catalytic magnesium hydride hydrogen storage material, comprising the following steps:

[0041] S1, using hydrofluoric acid aqueous solution to etch Nb2AlC and Ti3AlC2 in a one-step method to prepare two MXene materials, Nb2C and Ti3C2;

[0042] S2, by heat treatment, the -F functional groups in Nb2C and Ti3C2 are removed respectively, and -OH is converted into -O to obtain MXene materials: Nb2C / C and Ti3C2 / C;

[0043] S3, Nb2C / C, Ti3C2 / C and MgH2 were compounded by ball milling to prepare double MXene synergistic catalytic magnesium hydride hydrogen storage material.

[0044] In step S1 of the above preparation process, the chemical reaction equations for etching Nb2AlC and Ti3AlC2 respectively using hydrofluoric acid aqueous solution are: 2Nb2AlC+6HF→2Nb2C+2AlF3+3H2↑; 2Ti3AlC2+6HF→2Ti3C2+2AlF3+3H2↑. In this process, an excess of hydrofluoric acid aqueous solution is added, and the obtained AlF3 is dissolved in the solution. After heat treatment in step S2, the inserted / adsorbed water molecules are removed, and -OH is converted to -O. The increase of surface -O groups is beneficial to the redox reaction of hydrogen storage materials, while the removal of water is beneficial to the cycle performance of hydrogen storage materials.

[0045] Example 1

[0046] A double MXene synergistic catalytic magnesium hydride hydrogen storage material is prepared by the following steps:

[0047] (1) One-step etching of Nb2AlC: 20 mL of 40% HF aqueous solution was added to 1 g of Nb2AlC powder, stirred at 60°C for 70 h, and then centrifuged and washed at a speed of 10,000 rpm. The mixture was washed with deionized water several times until the pH value of the supernatant was 6-7. The precipitate A was filtered and freeze-dried for 70 h to obtain Nb2C powder.

[0048] (2) One-step etching of Ti3AlC2: 20 mL of 40% HF aqueous solution was added to 1 g of Ti3AlC2 powder, stirred at 60°C for 24 h, and then centrifuged and washed at a speed of 10,000 rpm. The mixture was washed with deionized water several times until the pH value of the supernatant was 6-7. The obtained precipitate B was freeze-dried for 70 h to obtain Ti3C2 powder.

[0049] (3) Heat treatment: The obtained Nb2C powder and Ti3C2 powder were respectively placed in a corundum crucible, and then the crucible was placed in a tubular furnace filled with Ar at 600°C and a heating rate of 4°C·min -1 and annealed for 6 h under the conditions of , and Nb2C / C powder and Ti3C2 / C powder were obtained respectively.

[0050] (4) Mechanical ball milling composite: The obtained Nb2C / C powder and Ti3C2 / C powder were mixed in a mass ratio of 1:2 to obtain a dual catalyst mixed powder, and the dual catalyst mixed powder was added to magnesium hydride powder at a weight percentage of 5wt% to obtain a mixture A, and then the mixture A was poured into a 50mL ball mill at a ball-to-material ratio of 40:1, and ball milled at a speed of 400rpm for 10h. The ball mill cycle program was set to forward rotation for 15mins, stop for 15mins, then reverse for 15mins, and stop for 15mins to obtain a composite hydrogen storage material. The final product was recorded as MgH2+Nb2C / 2Ti3C2 / C.

[0051] Example 2

[0052] Different from Example 1, in step (4) of this example, the obtained Nb2C / C powder and Ti3C2 / C powder are mixed in a mass ratio of 1:1, and the final product is recorded as MgH2+Nb2C / Ti3C2 / C.

[0053] Example 3

[0054] Different from Example 1, in step (4) of this example, the obtained Nb2C / C powder and Ti3C2 / C powder are mixed in a mass ratio of 2:1, and the final product is recorded as MgH2+2Nb2C / Ti3C2 / C.

[0055] Example 4

[0056] Different from Example 1, in step (4) of this example, the dual catalyst mixed powder is added to the magnesium hydride powder at a weight percentage of 3 wt%, and the final product is recorded as MgH2+3%Nb2C / 2Ti3C2 / C.

[0057] Example 5

[0058] Different from Example 1, in step (4) of this example, the dual catalyst mixed powder is added to the magnesium hydride powder at a weight percentage of 7 wt%, and the final product is recorded as MgH2+7%Nb2C / 2Ti3C2 / C.

[0059] Comparative Example 1

[0060] In an argon environment of a vacuum glove box, the Nb2C / C powder prepared in step (3) of Example 1 was added to the magnesium hydride powder at a weight percentage of 5 wt% to obtain a mixture B, and then the mixture B was poured into a 50 mL ball mill at a ball-to-material ratio of 40:1, and ball milled at a speed of 400 rpm for 10 h. The ball mill cycle program was set to forward rotation for 15 mins, stop rotation for 15 mins, then reverse rotation for 15 mins, and stop rotation for 15 mins. The final product was recorded as MgH2+Nb2C / C.

[0061] Comparative Example 2

[0062] In an argon environment of a vacuum glove box, the Ti3C2 / C powder prepared in step (3) of Example 1 was added to magnesium hydride powder at a weight percentage of 5 wt% to obtain a mixture C. The mixture C was then poured into a 50 mL ball mill at a ball-to-material ratio of 40:1, and ball milled at a speed of 400 rpm for 10 h. The ball mill cycle program was set to forward rotation for 15 mins, stop for 15 mins, then reverse for 15 mins, and stop for 15 mins. The final product was recorded as MgH2+Ti3C2 / C.

[0063] Based on the above embodiments, the following experiments were conducted:

[0064] 1. X-ray diffraction experiments of Nb2AlC and Nb2C / C

[0065] The crystal structure of Nb2C / C was determined by X-ray diffraction experiment. Taking the Nb2C / C prepared in step (3) of Example 1 as an example, the results are as follows: Figure 1 As shown. Figure 1 The XRD images of the prepared Nb2C / C and the original Nb2AlC can be seen. From the XRD images, it can be seen that the characteristic peak (38.9°) of Nb2AlC disappears after etching, proving that the preparation of Nb2C / C is successful.

[0066] 2. X-ray diffraction experiments of Ti3AlC2 and Ti3C2 / C

[0067] The crystal structure of Ti3C2 / C was determined by X-ray diffraction experiment. Taking Ti3C2 / C prepared in step (3) of Example 1 as an example, the results are as follows: Figure 2 As shown. Figure 2 The XRD images of the prepared Ti3C2 / C and the original Ti3AlC2 can be seen. From the XRD images, it can be seen that the characteristic peak (38.9°) of Ti3AlC2 disappears after etching, proving that the Ti3C2 / C is successfully prepared.

[0068] 3. SEM experiment of Ti3C2 / C and Nb2C / C samples

[0069] The microstructure of Ti3C2 / C and Nb2C / C samples was observed by scanning electron microscopy experiments, taking the Ti3C2 / C and Nb2C / C samples prepared in step (3) of Example 1 as an example. Figure 3 The SEM image of the prepared Ti3C2 / C sample is shown. Figure 4 The SEM images of the prepared Nb2C / C samples are shown. Specifically, Figure 3 (a) shows the SEM image of Ti3C2 observed at 20,000 times magnification; Figure 3 (b) shows the SEM image of Ti3C2 observed at 5000 times magnification; Figure 4 (a) is the SEM image of Nb2C observed at 20000 times magnification; Figure 4 (b) is the SEM image of Nb2C observed at 5000 times magnification. Figure 3 and Figure 4 It can be seen that Ti3C2 / C and Nb2C / C samples show a clean surface and an accordion-shaped uniform layered structure, indicating that the layered structure of MXene has been successfully synthesized. Compared with general catalysts, the MXene structure has a larger specific surface area and can provide more active sites. Its special structure can effectively increase the migration speed of ions.

[0070] 4. Energy dispersive X-ray spectroscopy experiments on Ti3C2 / C and Nb2C / C samples

[0071] The elements in the Ti3C2 / C and Nb2C / C samples were qualitatively analyzed by energy dispersive X-ray spectroscopy experiments. Taking the Ti3C2 / C and Nb2C / C samples prepared in step (3) of Example 1 as an example, Figure 5 is the EDS image of Ti3C2 / C, Figure 6 The EDS image of Nb2C once again proves that Ti3C2 / C and Nb2C / C are successfully synthesized, and there are different degrees of aluminum residues in them, which is due to partial exfoliation. This is consistent with the results of X-ray diffraction (XRD).

[0072] 5. Hydrogen desorption kinetics measurement experiment of different samples

[0073] The hydrogen desorption performance of the prepared samples was tested by hydrogen desorption kinetics measurement experiment. The hydrogen desorption performance of the samples prepared in Examples 1-5 and Comparative Examples 1-2 at 300°C and 0.01Mpa was tested by using a fully automatic Sievert desorber Gaspro. The results are shown in FIG. Figure 7 and Figure 8 Specifically, Figure 7The hydrogen desorption curves of MgH2+Nb2C / 2Ti3C2 / C of Example 1, MgH2+Nb2C / Ti3C2 / C of Example 2, MgH2+2Nb2C / Ti3C2 / C of Example 3, MgH2+Nb2C / C of Comparative Example 1 and MgH2+Ti3C2 / C of Comparative Example 2 show that the amount of hydrogen released by MgH2+Nb2C / 2Ti3C2 / C is higher than that of the dual MXene samples of other proportions at any time, and also higher than that of the samples catalyzed by a single MXene. In particular, MgH2+Nb2C / 2Ti3C2 / C can release 6.71wt% (92.9% of the theoretical hydrogen release) of H2 within 240s. Under the same conditions, MgH2+Ti3C2 / C can only release 5.99wt% of H2 (82.9% of the theoretical hydrogen release), and MgH2+Nb2C / C can only release 5.20wt% of H2 (72.0% of the theoretical hydrogen release). This shows that MgH2+Nb2C / 2Ti3C2 / C can greatly improve the hydrogen release kinetics of magnesium hydride while retaining as much hydrogen release as possible from MgH2.

[0074] Figure 8 The dehydrogenation curves of the composite hydrogen storage material prepared in Example 1 (recorded as MgH2+5%Nb2C / 2Ti3C2 / C), the MgH2+3%Nb2C / 2Ti3C2 / C sample in Example 4, and the MgH2+7%Nb2C / 2Ti3C2 / C sample in Example 5 are shown to explore the effect of different concentrations on the dehydrogenation effect of MgH2 at 300°C. As can be seen from the figure, when the dual catalyst mixed powder is added to the magnesium hydride powder at a weight percentage of 5wt%, MgH2 can release 6.71wt% of H2 within 6 minutes at this concentration, so adding 5wt% of the dual catalyst mixed powder to the magnesium hydride powder is the optimal catalyst concentration.

[0075] VI. Hydrogen absorption kinetics measurement experiment of different samples

[0076] The hydrogen absorption kinetics measurement experiment was used to detect the hydrogen absorption performance of the prepared samples. The fully automatic Sievert type hydrogen absorption instrument Gaspro was used to test the hydrogen absorption performance of the samples prepared in Examples 1-5 and Comparative Examples 1-2 at 200°C and 6Mpa. The results are shown in FIG. Fig. 9 and Fig.10 As shown, specifically, Fig. 9The hydrogen absorption curves of MgH2+Nb2C / 2Ti3C2 / C of Example 1, MgH2+Nb2C / Ti3C2 / C of Example 2, MgH2+2Nb2C / Ti3C2 / C of Example 3, MgH2+Nb2C / C of Comparative Example 1 and MgH2+Ti3C2 / C of Comparative Example 2 show that the amount of hydrogen absorbed by MgH2+Nb2C / 2Ti3C2 / C is higher than that of the dual MXene samples of other proportions, and even higher than that of the samples catalyzed by a single MXene. In particular, MgH2+Nb2C / 2Ti3C2 / C can absorb 5.45wt% (75.5% of the theoretical hydrogen absorption capacity) of H2 within 20s. Under the same conditions, MgH2+Ti3C2 / C can only absorb 5.06wt% of H2 (70.1% of the theoretical hydrogen absorption capacity), while MgH2+Nb2C / C can only absorb 4.90wt% of H2 (67.9% of the theoretical hydrogen absorption capacity). This shows that MgH2+Nb2C / 2Ti3C2 / C can retain as much hydrogen absorption capacity of MgH2 as possible.

[0077] Fig.10 The composite hydrogen storage material prepared in Example 1 (denoted as MgH2+5%Nb2C / 2Ti3C2 / C), as well as the hydrogen absorption curves of the MgH2+3%Nb2C / 2Ti3C2 / C sample of Example 4 and the MgH2+7%Nb2C / 2Ti3C2 / C sample of Example 5 are shown to explore the effect of different concentrations on the hydrogen absorption effect of MgH2 at 200°C. As can be seen from the figure, when the dual catalyst mixed powder is added to the magnesium hydride powder at a weight percentage of 7wt%, MgH2 can absorb 5.71wt% of hydrogen in 30 seconds, while when added at a weight percentage of 7wt%, it absorbs 5.44wt%. Finally, the hydrogen absorption capacity of the samples of the two concentrations tends to be the same after long-term hydrogen absorption. Considering the hydrogen absorption / desorption performance comprehensively, adding the dual catalyst mixed powder to the magnesium hydride powder at a weight percentage of 5wt% is considered to be the optimal catalyst concentration, because it can release the maximum mass concentration of hydrogen in a very short time while maintaining a large hydrogen absorption capacity.

[0078] In summary, the preparation flow chart of double MXene synergistic catalytic magnesium hydride hydrogen storage material is as follows Fig.11 As shown, the present invention utilizes a combination of two Nb2C / C and Ti3C2 / C catalysts, which significantly improves the hydrogen absorption / desorption kinetics of MgH2 through synergistic effect, and its catalytic effect is significantly better than that of a single catalyst. The present invention adopts a one-step etching process to prepare MXene at low temperature (<80°C), which simplifies the preparation process, reduces costs, and improves efficiency.

[0079] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a double MXene synergistic catalytic magnesium hydride hydrogen storage material, characterized in that: The following steps are involved: S1, using hydrofluoric acid aqueous solution to etch Nb2AlC and Ti3AlC2 in a one-step method to prepare two MXene materials, Nb2C and Ti3C2; S2, by heat treatment, the -F functional groups in Nb2C and Ti3C2 are removed respectively, and -OH is converted into -O to obtain MXene materials: Nb2C / C and Ti3C2 / C; S3, Nb2C / C, Ti3C2 / C and MgH2 were compounded by ball milling to prepare double MXene synergistic catalytic magnesium hydride hydrogen storage material.

2. The method for preparing the double MXene synergistic catalytic magnesium hydride hydrogen storage material according to claim 1, characterized in that: In step S1, one-step etching of Nb2AlC using hydrofluoric acid aqueous solution includes the following steps: mixing an excess hydrofluoric acid aqueous solution with a concentration of 40% with Nb2AlC powder, stirring at 60°C for 70 hours, centrifuging and washing until the pH value of the supernatant is 6-7, and then filtering, and freeze-drying the obtained precipitate A for 24-70 hours to obtain Nb2C powder.

3. The method for preparing the double MXene synergistic catalytic magnesium hydride hydrogen storage material according to claim 1, characterized in that: In step S1, one-step etching of Ti3AlC2 using hydrofluoric acid aqueous solution includes the following steps: mixing an excess hydrofluoric acid aqueous solution with a concentration of 40% with Ti3AlC2 powder, stirring at 60°C for 24 hours, centrifuging and washing until the pH value of the supernatant is 6-7, and then filtering, and freeze-drying the obtained precipitate B for 24-70 hours to obtain Ti3C2 powder.

4. The method for preparing the double MXene synergistic catalytic magnesium hydride hydrogen storage material according to any one of claims 2 or 3, characterized in that: The mixture was centrifuged at a speed of 10,000 rpm, and then washed with deionized water for multiple times until the pH value of the supernatant was 6-7.

5. The method for preparing the double MXene synergistic catalytic magnesium hydride hydrogen storage material according to claim 1, characterized in that: In step S2, the heat treatment step is: respectively put Nb2C powder and Ti3C2 powder into a crucible, then put the crucible into a tube furnace filled with inert gas, and heat at 600°C and a heating rate of 4°C·min -1 and annealed for 6 h under the conditions of , and Nb2C / C powder and Ti3C2 / C powder were obtained respectively.

6. The method for preparing the double MXene synergistic catalytic magnesium hydride hydrogen storage material according to claim 5, characterized in that: In step S3, the ball milling step is: mixing Nb2C / C powder and Ti3C2 / C powder in a mass ratio of 1:1-2 to obtain a dual catalyst mixed powder, adding the dual catalyst mixed powder to magnesium hydride powder to obtain a mixture A, and then pouring the mixture A into a ball mill for ball milling.

7. The method for preparing the double MXene synergistic catalytic magnesium hydride hydrogen storage material according to claim 6, characterized in that: The dual catalyst mixed powder is added to the magnesium hydride powder at a weight percentage of 3wt%-7wt%.

8. The method for preparing the double MXene synergistic catalytic magnesium hydride hydrogen storage material according to claim 6, characterized in that: The ball mill is a planetary ball mill; the mixture A is poured into the planetary ball mill and mechanically ball-milled at a rotation speed of 400 rpm for 10-20 hours; the ball-to-material mass ratio of the ball mill is 40:

1.

9. The method for preparing the double MXene synergistic catalytic magnesium hydride hydrogen storage material according to claim 6, characterized in that: The cycle program of the ball mill is set to rotate forward for 15 minutes, stop for 15 minutes, reverse for 15 minutes, and stop for 15 minutes, and the ball mill is operated alternately according to this program.

10. A dual MXene synergistic catalytic magnesium hydride hydrogen storage material, characterized in that: The material is obtained by the preparation method of the double MXene synergistic catalytic magnesium hydride hydrogen storage material as described in any one of claims 1 to 9.